CHILD PARENTING AND THE OCCURRENCE OF MALNOURISHED TODDLERS (HEALTH STUDIES IN THE WORKING AREA OF MONTASIK HEALTH CENTER, KEC. MONTASIK, KAB. ACEH BESAR) - Emiralda (Indonesian Journal of Medical Anthropology, 2022)
This study discusses the parenting of children against the occurrence of malnourished toddlers in Montasik Health Center, Kab. Aceh Besar in 2006. The purpose of this study is to find out the relationship between the influence of parenting in the form of the person in charge of parenting, the type of food given, meal time, frequency of eating, how to feed, the atmosphere and who feeds the malnourished toddler. The study used cross sectional designs on 150 toddlers (ages 12 months – 59 months) and their parents in the working area of Montasik Health Center. The results of the study showed that the parenting of children who affect the occurrence of toddler malnutrition is the type of food given, the frequency of eating, and the dominant influence is the type of food given that has an influence three times greater than the frequency of eating.